An improved model for the back-EMF and cogging torque characteristics of a novel axial flux permanent magnet synchronous machine with a segmental laminated stator - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong (IEEE, 2009)
An improved model for the back-electromagnetic-force (back-EMF) and cogging torque characteristics of a novel axial flux permanent magnet (AFPM) synchronous machine with a segmental laminated stator is presented. Based on a 3-D finite-element analysis (FEA) modeling approach that takes into the anisotropic properties of the machine's laminated cores, the proposed model provides superior performance prediction to existing isotropic models, in which lamination effects are not considered. An anisotropic model has been developed to predict the back-EMF and cogging torque of an existing prototype AFPM machine with optimized rotor magnets. Experimental results of the AFPM machine are compared against the results from the FEA models based on anisotropic and isotropic modeling, respectively. The results show that anisotropic modeling provides more accurate performance prediction of the AFPM machine with laminated cores.
Keywords: Anisotropic modeling axial flux permanent magnet (AFPM) machines isotropic modeling segmental laminated stator